Armenian Architecture through the Pages of Robert G. Ousterhout’s Book “Eastern Medieval Architecture: The Building Traditions of Byzantium and Neighboring Lands” - Kazaryan, Armen (Actual Problems of Theory and History of Art, 2019)
In his new monograph, along with the Byzantine regions, R. Ousterhout pays attention to the architecture of countries that surrounded Byzantium. Among the topics discussed in R. Ousterhout’s multifaceted new book, one is of particular interest to the author of this article, as it is connected to his own research.That is an issue of medieval Armenian architecture in the context of the architecture of the Byzantine world and the entire East. R. Ousterhout points out the role of the Roman heritage in early Christian Armenia. Following the descriptionof the Surb Khach church on Aghtamar Island (915–921), the author focuses on the metropolitancity of Ani and its Cathedral, which are compared by scholars to the churches of the European Romanesque. At the same time the author distinguishes the structure of Armenian and European buildings. Mentioning the zhamatun of Horomos monastery (1038) and the same-type constructions of the 13th century, R. Ousterhout insists on their uniqueness. In the chapter devoted to the master builders the author turns to a schematic working drawing of a stalactite vault executed on the wall of the gavit of the Astvatsnkal monastery. He analyzes photos of the drawing, which was lost for years and re-discovered during our expedition in May 2015. The author was able to give capacious characteristics to a variety of monuments, as well as emphasize those features that turned out to be especially significant to the specialists in Byzantine architecture.
Keywords: Robert G. Ousterhout; The Building Traditions of Byzantium; Armenian architecture; Roman heritage; Ani Cathedral; zhamatun of Horomos; drawing of a stalactite vault